2006
DOI: 10.1080/08098130609478164
|View full text |Cite
|
Sign up to set email alerts
|

Song Collage Technique: A New Approach to Songwriting

Abstract: Song Collage Technique is a therapeutic songwriting intervention. The presentation and discussion of this technique provides music therapy clinicians with detailed resources, consistent terminology with which to describe treatment, and therapeutic applications for clients who have cognitive impairments, difficulty articulating feelings due to cultural or gender issues, or time restrictions in therapy. A discussion of traditional therapeutic songwriting techniques provides a foundation for the evolution of Song… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…A large survey of clinicians found that some of the most common reasons for employing songwriting with clients were to assist them to: (a) externalize their thoughts, fantasies, and emotions: (b) tell their story: (c) develop a sense of self; and (d) gain insight or clarify thoughts and feelings . The songwriting process documented by many authors in Baker and Wigram's (2005) text on songwriting methods and other authors (for example : Baker, Kennelly, & Tamplin, 2005a, 2005bDalton & Krout, 2006;McFerran, Baker, Patton, & Sawyer, 2006;O'Callaghan, 1996;Silverman, 2003;Tamplin, 2006) allow clients a therapeutic space to express and reframe their thoughts and feelings, and construct a creative representation of them in the form of a song. The researchers propose that songwriting maybe a suitable approach for students to express and deepen their thoughts and feelings around training to be a music therapist.…”
Section: Songwritingmentioning
confidence: 99%
“…A large survey of clinicians found that some of the most common reasons for employing songwriting with clients were to assist them to: (a) externalize their thoughts, fantasies, and emotions: (b) tell their story: (c) develop a sense of self; and (d) gain insight or clarify thoughts and feelings . The songwriting process documented by many authors in Baker and Wigram's (2005) text on songwriting methods and other authors (for example : Baker, Kennelly, & Tamplin, 2005a, 2005bDalton & Krout, 2006;McFerran, Baker, Patton, & Sawyer, 2006;O'Callaghan, 1996;Silverman, 2003;Tamplin, 2006) allow clients a therapeutic space to express and reframe their thoughts and feelings, and construct a creative representation of them in the form of a song. The researchers propose that songwriting maybe a suitable approach for students to express and deepen their thoughts and feelings around training to be a music therapist.…”
Section: Songwritingmentioning
confidence: 99%
“…The narrative approach enables discussion between individuals experiencing TBI, their families and service providers, encouraging empowerment and post-traumatic growth (Ownsworth, 2014). The narrative approach enables opportunities for individuals experiencing TBI to express gratitude to family, friends (Tamplin, 2006), and in this study, service providers, for their support during the rehabilitation process. It provided a non-confrontational way to engage family members in the transition process, promoting honesty, reconnection and forgiveness.…”
Section: Discussionmentioning
confidence: 96%
“…As identified in other studies (Hogan, 1999;Tamplin, 2006), the narrative approach produces a range of valuable outputs and can lead to other outreach opportunities for the individual living with TBI. Digital storytelling, as used in this study, is particularly valuable in the context of Indigenous Australians.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cuando el paciente todavía se puede expresar verbalmente, escuchar y componer canciones (songwriting) es una forma poderosa de identificar emociones espontáneamente, expresarse, explicar historias, evitando así procesos de pensamiento concretos y mecanismos de defensa (Heath et al, 2012;Tamplin, 2006).…”
Section: Expresión "Sarandonga Esto Es Lo Que Te Quiero Decir"unclassified